Retrograde and direct powered aero-gravity-assist trajectories around mars - Murcia, J. O.; Prado, A. F.B.A.; Gomes, V. M. [UNESP] (My University, 2018)
A Gravity-Assist maneuver is used to reduce fuel consumption and/or trip times in interplanetary missions. It is based in a close approach of a spacecraft to a celestial body. Missions like Voyager and Ulysses used this concept. The present paper performs a study of a maneuver that combines three effects: the gravity of the planet, the application of an impulsive maneuver when the spacecraft is passing by the periapsis and the effects of the atmosphere of the planet. Direct and retrograde trajectories are considered, with particular attention to the differences due to the higher relative velocity between the spacecraft and the atmosphere, which increases the effects of the atmosphere. The planet Mars is used for the numerical examples.
Keywords: Celestial mechanics; Planets and satellites: atmospheres; Space vehicles